Knowledge, Creation, Diffusion and Utilization; Newspaper Research Journal; Who Reads and Why?; Daily Newspaper Non-Readers: Why They Don't Read - Larry Meiller; William E. Tedrick (Journal of Applied Communications, 1980)
Reviews of Knowledge, Creation, Diffusion and Utilization ; Newspaper Research Journal; "Who Reads and Why?" by George F. McEvoy and Cynthia S. Vincent; and "Daily Newspaper Non-Readers: Why They Don't Read," by Paula Poindexter